KINERJA ORGANISASI, PENAMPILAN PROFESIONAL, DAN KESEJAHTERAAN EKONOMI: TELAAH TEORITIS DALAM PERSPEKTIF MAQASID SYARIAH - Edi Marjan Nasution; Salwa Selvia; Royhan Musthofa Nasution; Bayu Purnomo; Bungsu Bungsu; Saniah Hilma Lubis; Resky Hasyim Syah (CV. Denasya Smart Publisher, 2026)
This study examines the relationship between professional appearance, economic welfare, and organizational performance through the lens of maqasid syariah using a literature review approach. Through a synthesis of organizational management, social psychology, and Islamic economics literature, this study identifies the mechanisms by which professional performance functions as a legitimacy signal and credibility that influences motivation, employee trust, and public perception. Economic welfare is analyzed not merely as a monetary variable but as a multidimensional construct that includes protection of life (hifz al-nafs), protection of property (hifz al-mal), and protection of honor (hifz al-'irdh). The proposed conceptual framework places welfare as a mediator and moderator, but also facilitates the capacity of individuals to meet professional appearance standards and strengthens the effect of appearance on performance. Maqasid sharia serves as a normative criterion for assessing whether appearance and welfare policies produce fair benefits and respect the dignity of employees. The theoretical contribution of this research is the integration of impression management, signaling, and legitimacy theories with the principles of maqasid syariah to understand micro and macro relationships within organizations. The main limitation is the nature of the literature review, which requires further empirical verification. Further research is recommended to develop maqasid syariah instruments and test integrative models quantitatively or experimentally. These findings are relevant for policymakers and managers who wish to balance performance objectives with ethical responsibilities, as well as encourage participatory dialogue in organizational policy formulation and promote maqasid syariah-based evaluation.